Impact of The Method of Diagnosis on The Stage of Breast Carcinoma - ERDİM, AYLİN (AVES, 2018)
Objective: Screening mammography is recommended to women at a certain age to achieve an early diagnosis. The purpose of this study is to find out how breast carcinoma was diagnosed and the impact of the method of diagnosis on the stage of the tumor. Materials and Methods: In this study, 903 operated breast cancer patients, between 2010-2016, in a large volume Marmara University Istanbul Pendik Education and Research Hospital were analyzed retrospectively. Patients presenting with clinical symptoms and those diagnosed with screening were investigated separately. The percentage of the patients diagnosed with symptoms and the impact of the method of diagnosis on the stage of the tumor was the primary outcome of the study. Results: 738 patients fulfilling inclusion criteria with complete clinical records were analyzed. 126 patients (17%) were in the age range of 19-39 years, while 32% (236 patients) were 40-50 and 51% (376 patients) were older than 50 years. 485 patients (65.7%) were diagnosed with a mass in the breast, while 241 (32.6%) patients were diagnosed with screening with mammography. Twelve patients (1.7%) presented with nipple discharge. Median tumor sizes measured in the resected specimen were 22 mm, 21 mm, and 21 mm in patients diagnosed with a mass, screening, and nipple discharge respectively. The difference among the groups were not significant (p=0.460). Axillary lymph nodes were positive in 210 (43.3%) of patients presenting with a mass in the breast while 85 patients (35.3%) diagnosed with screening had metastatic lymph nodes in the axilla. Three patients presenting with nipple discharge had positive axillary lymph nodes (p=0.137). Conclusion: This study demonstrated that breast cancer screening programs in Turkey needs improvement and at the same time shows that screening with mammography after 40 years of age should be done annually despite Ministry of Health recommendations.
Keywords: Patient; breast cancer; mass; screening; discharge; CANCER; TURKEY; HEALTH